2015
DOI: 10.1093/jamia/ocv156
|View full text |Cite
|
Sign up to set email alerts
|

Assessing race and ethnicity data quality across cancer registries and EMRs in two hospitals

Abstract: To facilitate transparent reporting of healthcare delivery outcomes by race/ethnicity, healthcare systems need to monitor and enforce race/ethnicity data collection standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Inconsistencies of race and ethnicity were reported between the birth and death of US infants; there was higher agreement for those who identified as White (1.2 %) and Black (4.3 %) and lower for those identified as Hispanic (30.3 %) [8]. Lee and colleagues analyzed the agreement of race and ethnicity between cancer registries and an electronic medical record and found that there was only complete agreement in 39.2 % of pairs; pairs with “black” data value labels had the highest agreement (95.3 %) and pairs with “other” data value labels had the lowest agreement across sources (11.1 %) [9]. The assessment of the validity of race/ethnicity in Medicare databases found that those who were recorded as White and Black in the Medicare electronic health record had better concordance with their self-report data than those who were identified as Hispanic, Asian, Pacific Islanders, American Indians, and Alaskan Natives (39–60 % agreement) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies of race and ethnicity were reported between the birth and death of US infants; there was higher agreement for those who identified as White (1.2 %) and Black (4.3 %) and lower for those identified as Hispanic (30.3 %) [8]. Lee and colleagues analyzed the agreement of race and ethnicity between cancer registries and an electronic medical record and found that there was only complete agreement in 39.2 % of pairs; pairs with “black” data value labels had the highest agreement (95.3 %) and pairs with “other” data value labels had the lowest agreement across sources (11.1 %) [9]. The assessment of the validity of race/ethnicity in Medicare databases found that those who were recorded as White and Black in the Medicare electronic health record had better concordance with their self-report data than those who were identified as Hispanic, Asian, Pacific Islanders, American Indians, and Alaskan Natives (39–60 % agreement) [1].…”
Section: Introductionmentioning
confidence: 99%
“…We though believe that our data give a realistic estimate of the order of magnitude of the issue. d. Furthermore, these results may have been influenced by documentation disparities, which have been demonstrated to occur in a significant number of patients in similar studies [9,[42][43][44][45][46][47][48][49]. e. We have no data to estimate to which extent complications emerging in the course of treatment might have influenced the results of this study, though e.g.…”
Section: Discussionmentioning
confidence: 84%
“…37 It was difficult to use EHRs to identify AA patients, as race-ethnicity fields are commonly missing or inaccurate, even in settings that care mainly for minority patients. 38,39 In GUARDD, over 10% of patients told us their listing as Black race was wrong. We were also unable to identify and thus contact AA patients who were among the one-third who met all other EHR criteria for eligibility, but had missing race-ethnicity data.…”
Section: Discussionmentioning
confidence: 99%